PENGARUH RENDAMAN AKAR PASAK BUMI (Eurycoma longifolia) TERHADAP MASKULINISASI IKAN CUPANG (Betta splendens) - Rudini, Mahmud; Kuswanto, Eko; Listiana, Ika; Prathama, Achmad Yoga (Universitas Jambi, 2025)
Male betta fish have high commercial value as they are highly favored by many people. Efforts to increase the number of male fish can be carried out through masculinization. This research used a quantitative approach with an experimental method, employing a Completely Randomized Design (CRD) consisting of five treatments and three replications. The highest percentage of male betta fish was obtained in treatment P3, reaching 63.77%, while the lowest percentage was found in the negative control (K-), at 38.75%. Masculinization of betta fish through immersion in Eurycoma longifolia root extract resulted in the highest percentage of male fish when soaked for 8 hours, increasing the sex ratio by 25.02% compared to the untreated control (negative control). Meanwhile, the percentage difference between soaking in Eurycoma longifolia root extract for 8 hours at a concentration of 20 mg/L and administering 17alpha-methyltestosterone for 4 hours at a concentration of 2 mg/L (positive control) was 6.38%. The immersion method with different durations had a significant effect on the percentage of male betta fish. The best soaking duration was found in treatment P1, with a soaking time of 2 hours, resulting in the highest betta fish survival rate of 85% and a male percentage of 62.66%.